94.4k views
3 votes
find the response of the function at * (t=4) using Laplace transform (y() + 2y" + y = sint) y(0)=1, y (0)=-2, y"(0)=3 , y"(0)=0

1 Answer

1 vote

Considering you have four initial conditions (the last of which should probably read
y'''(0)=0), I'm assuming the ODE is


y^((4))(t)+2y''(t)+y(t)=\sin t

with
y(0)=1,
y'(0)=-2,
y''(0)=3, and
y'''(0)=0.

Take the Laplace transform of both sides, denoting the transform of
y(t) by
Y(s):


(s^4Y(s)-s^3y(0)-s^2y'(0)-sy''(0)-y'''(0))+2(s^2Y(s)-sy(0)-y'(0))+Y(s)=\frac1{s^2+1}

Solve for
Y(s):


(s^4+2s^2+1)Y(s)-s^3+2s^2-5s+4=\frac1{s^2+1}


Y(s)=(1+(s^3-2s^2+5s-4)(s^2+1))/((s^2+1)(s^4+2s^2+1))

Notice that


s^4+2s^2+1=(s^2+1)^2


\implies Y(s)=(1+(s^3-2s^2+5-4)(s^2+1))/((s^2+1)^3)

and simplify a bit to get


Y(s)=(s^5-2s^4+6s^3-6s^2+5s-3)/((s^2+1)^3)

Decompose
Y(s) into partial fractions:


(s^5-2s^4+6s^3-6s^2+5s-3)/((s^2+1)^3)=(a_0+a_1s)/(s^2+1)+(b_0+b_1s)/((s^2+1)^2)+(c_0+c_1s)/((s^2+1)^3)


s^5-2s^4+6s^3-6s^2+5s-3=(a_0+a_1s)(s^2+1)^2+(b_0+b_1s)(s^2+1)+(c_0+c_1s)


s^5-2s^4+6s^3-6s^2+5s-3=a_1s^5+a_0s^4+(2a_1+b_1)s^3+(2a_0+b_0)s^2+(a_1+b_1+c_1)s+(a_0+b_0+c_0)


\implies\begin{cases}a_1=1\\a_0=-2\\2a_1+b_1=6\\2a_0+b_0=-6\\a_1+b_1+c_1=5\\a_0+b_0+c_0=-3\end{cases}


\implies a_0=-2,a_1=1,b_0=-2,b_1=4,c_0=1,c_1=0

So we have


Y(s)=(s-2)/(s^2+1)+(4s-2)/((s^2+1)^2)+\frac1{(s^2+1)^3}

Split up the first term to get two easy inverse transforms:


L^(-1)\left[\frac s{s^2+1}\right]=\cos t


L^(-1)\left[-\frac2{s^2+1}\right]=-2\sin t

Also split up the second term, but use the convolution theorem, which says


L\left[(\alpha \ast \beta)(t)\right]=A(s)\cdot B(s)

where
A(s) and
B(s) are the Laplace transforms of
\alpha(t) and
\beta(t), respectively, and the convolution is defined by


(\alpha \ast \beta)(t)=\displaystyle\int_0^t\alpha(\tau)\beta(t-\tau)\,\mathrm d\tau

Take


A(s)=(4s)/(s^2+1)\text{ and }B(s)=\frac1{s^2+1}

so that


\alpha(t)=4\cos t\text{ and }\beta(t)=\sin t

and their convolution is


L^(-1)\left[(4s)/((s^2+1)^2)\right]=(\alpha \ast \beta)(t)=2t\sin t

Next, take


A(s)=-\frac2{s^2+1}\text{ and }B(s)=\frac1{s^2+1}


\implies \alpha(t)=-2\sin t\text{ and }\beta(t)=\sin t


\implies L^(-1)\left[-\frac2{(s^2+1)^2}\right]=t\cos t-\sin t

You can treat the third term similarly, but with an extra step. First compute


L^(-1)\left[\frac1{(s^2+1)^2}\right]

by taking


A(s)=B(s)=\frac1{s^2+1}


\implies \alpha(t)=\beta(t)=\sin t

Then


L^(-1)\left[\frac1{(s^2+1)^2}\right]=\frac{\sin t-t\cos t}2

Next, take


A(s)=\frac1{(s^2+1)^2}\text{ and }B(s)=\frac1{s^2+1}


\implies \alpha(t)=\frac{\sin t-t\cos t}2\text{ and }\beta(t)=\sin t


\implies L^(-1)\left[\frac1{(s^2+1)^3}\right]=\frac{(3-t^2)\sin t-3t\cos t}8

Thus we end up with the solution,


y(t)=(\cos t-2\sin t)+(2t\sin t+t\cos t-\sin t)+\frac{(3-t^2)\sin t-3t\cos t}8


\boxed{y(t)=\frac{(8+5t)\cos t+(-21+16t-t^2)\sin t}8}

User Shenae
by
4.7k points